Correlation between ovarian morphology and biochemical and hormonal parameters in polycystic ovary syndrome - (:unkn) unknown (PROFESSIONAL MEDICAL PUBLICATIONS, 2016)
Objective: To determine the biochemical and hormonal differences in polycystic ovary syndrome (PCOS) patients with and without polycystic ovary (PCO) morphology and to evaluate the outcomes resulting from those differences. Methods: The study included a total of 83 patients with PCOS; 43 of them had PCO morphology (Group-I) and 40 did not (Group-II). Serum LDL, HDL, total cholesterol, triglyceride (TG), total testosterone (T), follicle stimulating hormone (FSH), luteinizing hormone (LH), 17b-estradiol (E2), prolactin (PRL), thyroid stimulating hormone (TSH), sex hormone binding globulin (SHBG), glucose and insulin levels were determined. Homoeostatic model assessment insulin resistance (HOMA-IR) index was calculated. Results: The two groups were similar with respect to BMI. The systolic and diastolic blood pressure measurements of Group-I were significantly lower (p<0.01). Serum mean level of LH (p=0.026) and the mean LH/FSH (p=0.001) level of Group-I were significantly higher than Group-II. The total cholesterol and triglyceride levels of Group-I were significantly lower (p<0.05, p<0.01). The mean HOMA-IR level of Group-I was significantly lower than Group-II (p=0.004). Conclusions: The group without PCO morphology had a higher risk than the other group in terms of increased insulin resistance, dyslipidemia and cardiovascular diseases due to effects of hyperandrogenism.
Keywords: Hyperandrogenism; Insulin resistance; PCOS; PCO morphology; Total cholesterol; WOMEN